A\Study on Out Patient Satisfaction at a Super Specialty Hospital in India - S. K. Jawahar (Internet Journal of Medical Update, Vol. 2, No. 2, Jul-Dec 2007, 2007)
Patients and staff satisfaction is an important component of the health care industry in this competitive modern era. In the hospital, the Outpatient Department is often called "Shop Window". Patients' satisfaction leads to drift in both new and old patients, whichhinders the sustainability of any hospital in long run. This study was conducted to know the satisfaction level of patients and also get a feedback about the services provided in the outpatient departments. The patients were randomly selected and a questionnaire was developed to evaluate patient satisfaction about the outpatient department services, logistic arrangement in the outpatient departments, waiting time, facilities, perception about the performance of staff, appointment system, behavior of staff, support service and any other suggestions of patients. Out of 200 patients surveyed, 90-95 per centof patients were satisfied with the service offered in the hospital. This study also showed that some of the patients waiting time were prolonged and thefriendliness of the nursing staff needs to be improved.